Postern of Fate - Christie, Agatha (Glasgow William Collins Sons & Company, Ltd., 1980)
Tommy and Tuppence buy a home and find they have acquired a mystery which includes an unsolved murder.
English Fiction.
Keywords: Beresford, Tommy (Fictitious character) -- Beresford, Tuppence (Fictitious character) -- Private investigators